Biorefinery of sunflower by-products: Optimization of twin-screw extrusion for novel biostimulants - Jing Li; Hoang Khai Trinh; Lucas Tricoulet; Stéphane Ballas; Laurent Labonne; Danny Geelen; Philippe Evon (Heliyon)
In view of improving the circularity and sustainability of crop production, sunflower by-products were extracted using twin-screw extrusion (TSE) to produce sunflower extract, a plant biostimulant that alleviates plant shoot development under salt stress conditions. The TSE process is a thermo-mechano-chemical pre-treatment method for the separation of liquid fraction from the biofiber. To improve the cost-efficiency of extraction, we determined the key procedure of TSE extraction within the production chain for biostimulants derived from sunflower bark and heads. This study scrutinizes sample preparation and extraction methods optimizing the sunflower by-product biorefinery, reducing energy input and maximal recovery of biostimulant activity. Optimal extraction conditions were obtained with starting material ground to a coarse size of 6 mm on average in alkaline aqueous solvent (pH 10) at a liquid-to-solid ratio of 5.5 injected at two different points using a 3 D length of reversed screw elements at the rotation speed of 200 rpm. These TSE settings provide a reproducible protocol for the biostimulant extraction from sunflower by-products. The optimized method contributes to improving the profitability of sunflower production and contributes to a more robust biostimulant extraction procedure.